Reverberação, contaminação e reconstrução: a poética de Michel Gondry em A Espuma dos Dias - Santos, Rogério Pereira dos (2017)
Filmmaker Michel Gondry’s poetics is built around the creation of a fantastic environment, enhanced by dreamlike narratives filled with subjetivity. His work can be approximated to the French tradition, ranging from Georges Méliès to Jean Vigo and Albert Lamorisse, but it is also contaminated by the director’s experience with music vídeos and his predilection for analog aesthetics. This visual signature is instrumental for comprehending a crucial feature of Gondry’s work: he is na artist of the mise-en-scène. This element permeates his production and is manifest in his most recente film: L’Écumes des Jours, reconstructed from the homonymous Boris Vian's novel. This study, therefore, search for make explicit the fictional world of Vian now intensified by the peculiar artistic vision of Gondry. The transcreative aspects that involve the production of L’Écumes des Jours, the possible intersections between the literary work, the reflections on the big screen and the language of the French filmmaker are on the agenda of this essay. For this, a method of comparative analysis was developed between text and moving image from three concepts: reverberation, contamination and reconstruction. These are based on the ideas of dialogism and carnivalization of Mikhail Bakhtin. The final result is a cartography of Michel Gondry's poetics in L’Écumes des Jours, as well as the disclosure of the filmmaker's affinities and their complex creative processes: sometimes collaboratives, sometimes personal, full of free associations, stored in notebooks or VHS tapes, as intimate as possible. It is estimated that the method offers resources for studies involving different languages, especially those related to cinema and literature.